1,3-Dipolar Cycloaddition Reactions of N-Methyl-Substituted Tricyclic Imides - Goksu, Gokce; Ocal, Nuket (SLOVENSKO KEMIJSKO DRUSTVO, 2011)
The [3+2] cycloadditions of N-methyl derivatives of unsaturated imides with various nitrite oxides to yield new bridged isoxazoline derivatives with potential biological activity is described.
Keywords: Alkenes; cycloadditions; heterocycles; triyclic imides; cantharidin analogues; CYCLIC IMIDES; NITRILE OXIDES; DERIVATIVES; Chemistry